Risk of suicide in cancer patients in Western Australia, 1981-2002 - Dormer, N.; McCaul, Kieran; Kristjanson, Linda (Australasian Medical Publishing Company, 2008)
OBJECTIVE: To describe the incidence and risk of suicide in cancer patients in Western Australia from 1981 to 2002. DESIGN, SETTING AND PATIENTS: Retrospective cohort study of patients diagnosed with cancer in WA from 1981 to 2002, using data from the WA Linked Database. MAIN OUTCOME MEASURE: Age-standardised mortality ratios (SMRs). RESULTS: A total of 121 533 patients were diagnosed with cancer, corresponding to a total of 543 696 person-years at risk. There were 129 suicides in this group (108 in men). The SMR for suicide in cancer patients was 1.61 (95% CI, 1.36-1.92). An initial period of peak risk was seen in the first 3 months after cancer diagnosis (SMR, 5.75; 95% CI, 3.89-8.51), mainly in patients with a poor prognosis. A second peak period of risk was found to occur 12-14 months after diagnosis (SMR, 2.33; 95% CI, 1.11-4.89) in those with a good or moderate prognosis. CONCLUSION: The rate of suicide in cancer patients in WA is low and represents an excess of two to three suicides per year, or 0.3% of all cancer deaths, comparable to studies in other Western countries. The risk is highest in the first 3 months after diagnosis, and a second period of increased risk 12-14 months after diagnosis may occur in response to cancer recurrence or treatment failure.